2019
DOI: 10.17269/s41997-019-00229-w
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion in the workplaces: fostering resilience in times of organizational change

Abstract: Objectives In 2015, a healthcare reform was undertaken in the province of Quebec (Canada). This amended system resources and structures, resulting in increased work-related stress, retirements, and sick leaves. In this study, we examined associations between stress, psychological distress, and resilience in this context. Methods A subsample of healthcare workers (n = 1008) from the 2014-2015 Eastern Townships population-based survey was used to examine resilience, its distribution among various occupational ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Within the context of organizational change, resilience plays an important role in regulating employee responses and outcomes. Roy et al (2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms. Employees in organizations undergoing change also recovered significantly from the stress caused by change events after resilience-enhancement programs were introduced to effectively build resilience resources in employees (IJntema et al, 2021).…”
Section: Resilience In Response To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of organizational change, resilience plays an important role in regulating employee responses and outcomes. Roy et al (2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms. Employees in organizations undergoing change also recovered significantly from the stress caused by change events after resilience-enhancement programs were introduced to effectively build resilience resources in employees (IJntema et al, 2021).…”
Section: Resilience In Response To Covid-19mentioning
confidence: 99%
“…Within the context of organizational change, resilience plays an important role in regulating employee responses and outcomes. Roy et al. (2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms.…”
Section: Organizational Change In Response To Covid-19mentioning
confidence: 99%
“…Therefore, involvement practices might have an indirect effect on curbing psychosocial stressors (Giga et al, 2003). Such an indirect effect is activated via the mediating role of HPI, which concur in tackling sources of stress in the workplace (Roy et al, 2019). In sum, it is hypothesized that: H4.…”
Section: The Imperfections Of Employee Involvementmentioning
confidence: 99%
“…It is estimated that work stress affects three million workers worldwide [ 10 ], and that it represents between 50–60% of the cases of absenteeism and presenteeism [ 11 , 12 ]. In addition, several studies have reported that the health sector suffers the most from this type of problem [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the aforementioned, various organizations associated with health and work have the objective of promoting quality of life and well-being, as well as greater productivity, in the worker [ 11 , 45 ]. They consider of interest the creation of strategies and technological solutions for the early detection and control of factors and effects associated with work stress, as well as balance between personal and work life and the promotion of healthy habits [ 13 , 46 ].…”
Section: Introductionmentioning
confidence: 99%